2014
DOI: 10.2190/ag.79.1.d
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Related to Cognitive Functioning: A Cross-National Comparison of U.S. and Korean Older Adults

Abstract: The purpose of this study was to conduct a cross-national comparison of factors related to cognitive functioning in later life in a U.S. and Korean sample. The study sample was comprised of subjects from the HRS (N = 10,175) and the KLoSA (N = 3,550). Separate multivariate regression models were employed to examine the impact of socio-demographic, health, and health behaviors on cognitive functioning among older adults. Regression results showed that age, gender, education, wealth, self-rated health, ADL, IADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(39 reference statements)
2
10
2
Order By: Relevance
“…Examining cognitive impairment, more than three healthy behaviors were required to have a significant effect. Some literature suggests that there is little or no significant association between each healthy behavior and cognition among older adults . However, the present study result suggests the powerful effect of more than three combined healthy lifestyle factors on cognitive function exists.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Examining cognitive impairment, more than three healthy behaviors were required to have a significant effect. Some literature suggests that there is little or no significant association between each healthy behavior and cognition among older adults . However, the present study result suggests the powerful effect of more than three combined healthy lifestyle factors on cognitive function exists.…”
Section: Discussioncontrasting
confidence: 66%
“…Some literature suggests that there is little or no significant association between each healthy behavior and cognition among older adults. 15,31,32 However, the present study result suggests the powerful effect of more than three combined healthy lifestyle factors on cognitive function exists. According to Lee et al, a leisure activity incorporating more than two components (physical, social and mental) was associated with lower risk of dementia.…”
Section: Discussioncontrasting
confidence: 55%
“…In particular, our findings would complement findings from pre-existing populationbased cognitive aging studies in Koreans (i.e. the Korean Longitudinal Study on Health and Aging (KLoSHA), the Korean Longitudinal Study of Ageing), Memory and Aging Study of Koreans (MASK)) in understanding cognitive aging process of the Korean population (Lyu, Lee, and Dugan, 2014;Jang and Kim, 2015). KoGES provides unique data in that its study population consists of middle-aged and older population, which allowed us to capture performance from a pre-symptomatic population.…”
Section: Introductionsupporting
confidence: 60%
“…However, many studies reported that being a woman is a risk factor for cognitive impairment. 7 Gender differences in work and family roles may explain mental health disparities by gender. 8 Since women have lower education, lower wages, and less social benefits than men, disadvantages in socioeconomic structure could lead to gender differences in the prevalence of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies identifying gender-specific risk factors for cognitive impairment are rare, and if gender-specific models were examined, most studies were conducted in a cross-sectional design. 7 22 Since longitudinal studies examining predictors of cognitive impairment are few, it is not clear which gender-specific factors have causal relationships with cognitive impairment. Therefore, this study attempts to fill this gap and examine the gender-specific incidence and predictors of cognitive impairment, using a nationally representative sample of older Koreans from 2006 to 2012.…”
Section: Introductionmentioning
confidence: 99%